Processos de identidade na formação dos presbíteros católicos indígenas - Oliveira, Ademir Lima de (2019)
This research addresses the processes that lead to the constitution of the Indigenous Roman Catholic Presbyter's identity in the perspective of Social Psychology, taking into account the term "Identity-Metamorphosis-Emancipation" proposed by Ciampa as well as Habermas's theory on the formation of the individual in society. As case study, the inter-ethnic context in the Upper Course of Rio Negro (Brazil) was chosen, selecting participants from different ethnicities, ages and presbyterate years. As methodological approach, life-story and future-project narrative analyses were adopted to work with. Moreover, dialogues with Anthropology were necessary in order to deal with traditional populations. The analysis approach is used to understand and identify the sense of identity manifested in the narratives of the Indigeneous priests. A search for recognition is clearly associated with the perceptible metamorphoses present throughout the process that a presbyteral formation requires. It is possible to speak of emancipatory fragments, since the Indigenous never ceases to be who he is in order to assume the role of “the presbyter”. In fact, the two symbolic universes interact and complement each other in the performance of social roles. Therefore, the identity of the Indigenous priest does not only involve the performance of certain rituals in accordance with the tradition of the Roman Catholic Church, but also with the original customs of the Indigenous peoples. The research aims to point out how the constitution of the presbyteral identity occurs, based on the theoretical field to discuss the processes of socialization, identity policies with references to the official documents of the Catholic Church